2011
DOI: 10.1007/978-3-642-21028-0_40
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Identification in Cardiac Electrophysiology Using Proper Orthogonal Decomposition Method

Abstract: Abstract. We consider the problem of estimating some parameters (like ionic models or parameters involved in the initial stimulation) of a model of electrocardiograms (ECG) from the data of the Einthoven leads. This problem can be viewed as a first attempt to identify or to locate a pathology. The direct model is based on the bidomain equations in the heart and a Poisson equation in the torso and. To keep the computational time reasonable, the evaluation of the direct problem is approximated with a reduced ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
1
3
0
1
Order By: Relevance
“…We have observed that the DOE of a POD basis based on a single generating parameter is narrow, especially when the amplitude of the conductivity value is small. This phenomena has also been shown in [7] where POD was applied to estimate ionic model parameters. The situation in our case is even worse, considering the fact that we can not group snapshots for basis construction from different generating parameters, due to the strong sensitivity of the transmembrane potential to the conductivities.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…We have observed that the DOE of a POD basis based on a single generating parameter is narrow, especially when the amplitude of the conductivity value is small. This phenomena has also been shown in [7] where POD was applied to estimate ionic model parameters. The situation in our case is even worse, considering the fact that we can not group snapshots for basis construction from different generating parameters, due to the strong sensitivity of the transmembrane potential to the conductivities.…”
Section: Discussionsupporting
confidence: 61%
“…In constructing a reduced basis for the parameterized Monodomain model, two ways can be followed as mentioned in [7]. One is to store a set of solutions of the full-order model computed at different instants with a set of different parameter values in a given sample space, then collect all these solutions to build a unique snapshot matrix, upon which the POD basis is finally built.…”
Section: The Pod Basis For the Monodomain Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This may have interesting applications for long time simulations, for example to compute a restitution curve, or to estimate the ionic current parameters in an optimization loop. Second, a reduced-order model based on a single simulation is totally inadequate to approximate a situation with a spatial change in the parameter: this has been shown in the present study for an infarcted region; in [4] the same observation was made for the initial activation region. A natural strategy consisting of precomputing several POD bases with different sets of parameters, or a single POD basis from different experiments, proved to be satisfactory in the cases we have considered.…”
Section: Discussionmentioning
confidence: 53%
“…• des mesures moins invasives pour la personnalisation du modèle, remplaçant la mesure de potentiels électriques dans les ventricules par des mesures acquises sur le thorax du patient (ECG, VCG, cartes de potentiels thoraciques) [33]; • une simulation plus fine de la mécanique des fluides sanguins [34], qui peut bénéficier de techniques modernes d'imagerie comme l'IRM à contraste de phase; • une modélisation et une simulation plus fines de diverses formes de thérapie (resynchronisation cardiaque, ablation radiofréquence, chirurgie, pose de valves, etc.) [35]; • la simulation du remodelage du coeur après une thérapie et la modélisation du développement du coeur chez l'enfant [36] ; • la prise en compte des incertitudes de mesure et de modélisation [37] ;…”
Section: Conclusion Et Perspectives : Du Coeur Au Corps Numériqueunclassified